2022
DOI: 10.18632/aging.204006
|View full text |Cite
|
Sign up to set email alerts
|

Burden of lymphoma in China, 1990−2019: an analysis of the global burden of diseases, injuries, and risk factors study 2019

Abstract: Background: China is facing an aggravating disease burden of lymphoma. However, accurate information about lymphoma burden at the national and provincial levels is limited. Results: The estimated number of disability-adjusted life years were 86,171.85 for Hodgkin lymphoma and 1,306,247.77 for non-Hodgkin lymphoma with the age-standardized rates of 4.95 and 71.00, respectively, per 100,000 population. There were estimated 9,468 new cases and 2,709 Hodgkin lymphoma-related deaths, and 91,954 new cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Peripheral T/NK-cell lymphoma (PTCL) is a group of rare and highly heterogeneous malignant lymphoproliferative diseases originating from mature T- and NK-cells. PTCL is classified into subtypes such as angioimmunoblastic T-cell lymphoma (AITL), ALK-positive anaplastic large-cell lymphoma (ALK+ALCL), ALK-negative anaplastic large-cell lymphoma (ALK-ALCL), peripheral T-cell lymphoma not otherwise specified (PTCL-NOS), and so on ( 1 , 2 ). Most subtypes have a dismal prognosis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral T/NK-cell lymphoma (PTCL) is a group of rare and highly heterogeneous malignant lymphoproliferative diseases originating from mature T- and NK-cells. PTCL is classified into subtypes such as angioimmunoblastic T-cell lymphoma (AITL), ALK-positive anaplastic large-cell lymphoma (ALK+ALCL), ALK-negative anaplastic large-cell lymphoma (ALK-ALCL), peripheral T-cell lymphoma not otherwise specified (PTCL-NOS), and so on ( 1 , 2 ). Most subtypes have a dismal prognosis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…[2] A sub-analysis demonstrated that there were an estimated 9,468 new cases and 2,709 deaths due to HL, 91,954 new cases and 44,310 deaths due to NHL, and 18,790 new cases and 13,420 deaths due to MM in China in 2019. [3,4] The disease burden of lymphoma and MM will continue to be exacerbated because of population growth, aging and increasing prevalence of risk factors. [5] Autologous hematopoietic stem cell transplantation (AHSCT) is an important therapeutic strategy to improve the survival outcome of lymphoma and MM, and the number of cases treated with this therapy has been increasing in the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective study comprised a review of the clinical data of patients diagnosed between 1 st January 2007 and 30 st June 2021 at Peking University Cancer Hospital. The key inclusion criteria included ( 1 ) HBsAg-positive ( 2 ); confirmed diagnosis of DLBCL using a biopsy specimen ( 3 ); receipt of at least four cycles of R-CHOP immunochemotherapy; and ( 4 ) treated with prophylactic antivirals. The exclusion criteria comprised ( 1 ) involvement of the central nervous system; and ( 2 ) Human immunodeficiency virus or Hepatitis C virus coinfection.…”
Section: Methodsmentioning
confidence: 99%
“…The key inclusion criteria included ( 1 ) HBsAg-positive ( 2 ); confirmed diagnosis of DLBCL using a biopsy specimen ( 3 ); receipt of at least four cycles of R-CHOP immunochemotherapy; and ( 4 ) treated with prophylactic antivirals. The exclusion criteria comprised ( 1 ) involvement of the central nervous system; and ( 2 ) Human immunodeficiency virus or Hepatitis C virus coinfection. To evaluate the effect of infection with HBV on the prognosis of DLBCL, we chose a control group who were not infected with HBV (negative for both HBsAg and HBcAb).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation